Impact of Relative Humidity on Electrochemical Performance of MXene-Zn-CNC Composite Films - Rudy Fernandez; Hairul Abral; Ikhwana Elfitri (ASEAN Journal for Science and Engineering in Materials, 2025)
This study examines the influence of relative humidity (RH) on the electrochemical and structural properties of polyvinyl alcohol (PVA) composite films reinforced with MXene, zinc oxide (ZnO), and cellulose nanocrystals (CNC). Composite films were fabricated via solvent casting and conditioned at RH levels of 50%, 75%, and 94%. Cyclic voltammetry and four-point probe tests revealed substantial enhancements in current density, specific capacitance, and bulk conductivity with increasing RH, attributed to improved ionic mobility and interfacial polarization. X-ray diffraction indicated reduced crystallinity due to polymer swelling, while scanning electron microscopy showed enhanced MXene dispersion at higher RH. Fourier-transform infrared spectroscopy confirmed intensified hydroxyl interactions, reflecting increased hydrophilicity. These humidity-induced improvements suggest promising applications in humidity-responsive flexible electronics and sensors. However, potential trade-offs include reduced mechanical stability under prolonged exposure. The findings offer new insights for optimizing hydrophilic polymer composites to enhance environmental adaptability and advanced device performance.